2020
DOI: 10.1051/0004-6361/202037477
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulations of shear-induced consecutive coronal mass ejections

Abstract: Context. It is widely accepted that photospheric shearing motions play an important role in triggering the initiation of coronal mass ejections (CMEs). Even so, there are events for which the source signatures are difficult to locate, while the CMEs can be clearly observed in coronagraph data. These events are therefore called 'stealth' CMEs. They are of particular interest to space weather forecasters, since eruptions are usually discarded from arrival predictions if they appear to be backsided, which means n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…It has been suggested that apparently stealth CMEs result from observational limitations such as instrument sensitivity and bandwidth issues, even in the SDO era (Howard and Harrison, 2013), and that advanced image processing techniques may reveal hard-to-observe signatures in both solar disc and coronagraph imagery (Alzate and Morgan, 2017;O'Kane et al, 2019). Additionally, some studies have applied geometric triangulation and reconstruction techniques to data from complementary viewpoints in order to trace stealth CMEs back to an approximate source region on the disc (Pevtsov et al, 2012;O'Kane et al, 2019;Talpeanu et al, 2020). These methods, however, have not been tested on a large number of events and hence it is not known whether they are suitable to all circumstances or whether they can be applied only to a limited number of cases.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that apparently stealth CMEs result from observational limitations such as instrument sensitivity and bandwidth issues, even in the SDO era (Howard and Harrison, 2013), and that advanced image processing techniques may reveal hard-to-observe signatures in both solar disc and coronagraph imagery (Alzate and Morgan, 2017;O'Kane et al, 2019). Additionally, some studies have applied geometric triangulation and reconstruction techniques to data from complementary viewpoints in order to trace stealth CMEs back to an approximate source region on the disc (Pevtsov et al, 2012;O'Kane et al, 2019;Talpeanu et al, 2020). These methods, however, have not been tested on a large number of events and hence it is not known whether they are suitable to all circumstances or whether they can be applied only to a limited number of cases.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 22 shows simulation results from Talpeanu et al (2020) where they model the formation and eruption of a large reconnection-generated plasmoid in the flare current sheet of a CME launched from a southern hemisphere pseudostreamer. There are two interesting features to highlight: First, the preceding non-stealth CME driver, that is predominant in the top two panels, shows significant latitudinal deflection, as discussed by and who analyse and simulate an event observed on 21-22 September 2009 that resembles this eruption scenario.…”
Section: Stealth Cmes Originating From Streamer Disruptions and Reconnection Transientsmentioning
confidence: 99%
“…Bottom panels: Location of the front of the simulated CME (left side) and total speed calculated at the CME centre (right side) as a function of time for: black squares -the preceding eruption, and red starsthe stealth eruption (the reconnection-generated plasmoid). Adapted from Talpeanu et al (2020) greater coronal heights than CMEs from ARs or even high-latitude filament channels. While it remains to be seen just how often these non-CME transients produce coherent, geoeffective interplanetary ejecta, they should be considered as potential sources of stealth CMEs, with ambiguity in the precise source region and formation/initiation mechanism, until improved observational constraints become available.…”
Section: Stealth Cmes Originating From Streamer Disruptions and Reconnection Transientsmentioning
confidence: 99%
“…Figure 22 shows simulation results from Talpeanu et al (2020) where they model the formation and eruption of a large reconnection-generated plasmoid in the flare current sheet of a CME launched from a southern hemisphere pseudostreamer. There are two interesting features to highlight: First, the preceding non-stealth CME driver, that is predominant in the top two panels, shows significant latitudinal deflection, as discussed by Zuccarello et al (2012) and Bemporad et al (2012) who analyse and simulate an event observed on 21 -22 September 2009 that resembles this eruption scenario.…”
Section: Stealth Cmes Originating From Streamer Disruptions and Recon...mentioning
confidence: 99%
“…Bottom panels: Location of the front of the simulated CME (left side) and total speed calculated at the CME centre (right side) as a function of time for: black squares -the preceding eruption, and red stars -the stealth eruption (the reconnectiongenerated plasmoid). Adapted from Talpeanu et al (2020).…”
Section: Stealth Cmes Originating From Streamer Disruptions and Recon...mentioning
confidence: 99%